Analysis of Above-Ground Steel Storage Tanks Resting Over Piles or Stone Columns - Tarek Salem (Gruppo Italiano Frattura, 2021)
Static and dynamic behavior of above-ground steel storage oil tanks resting on end bearing piles or stone columns are studied and analyzed using ADINA (2019) program. The studied soil profile is an upper soft clay soil layer, followed by an extended dense sand layer. The main purpose of this research is to explore to what extent stone columns can be used as an effective alternative to concrete piles under steel storage tanks. Therefore, many three-dimensional numerical models are conducted to analyze and study the performance of such tanks in both static and dynamic cases. Ten of the studied cases are steel tanks resting over stone columns with different numbers and properties. On other hand, one model studied the behavior of steel tank resting on large diameter concrete piles. Results indicate that stone columns can be used instead of end bearing piles as long as the computed settlements are safe. In addition, stone columns are behaving better than concrete piles in decreasing of hoop stress in tank shell. It is also noticed that stone columns with high elastic modulus are effective in reducing the sloshing height of the oil surface during earthquakes.